2022
DOI: 10.1186/s12903-022-02194-2
|View full text |Cite
|
Sign up to set email alerts
|

Computer-controlled Intraligamentary local anaesthesia in extraction of mandibular primary molars: randomised controlled clinical trial

Abstract: BackgroundLocal anesthesia (LA) poses a threat in children more than the treatment process itself, so pediatric dentists are always demanding less painful techniques. Computer-controlled Intraligamentary anaesthesia (CC-ILA) is designed to reduce injection pain and side effects of conventional techniques. The present study aims to assess the pain experience using Computer-controlled Intraligamentary anaesthesia (CC-ILA) during injection and its effectiveness in controlling pain during extraction of mandibular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…High-pressure injections using a traditional syringe may harm the underlying permanent dental buds when anesthetizing the primary molars [ 8 ]. If ILA is administered with a high-pressure syringe, the periodontal tissue may be damaged, which prolongs postoperative pain [ 3 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…High-pressure injections using a traditional syringe may harm the underlying permanent dental buds when anesthetizing the primary molars [ 8 ]. If ILA is administered with a high-pressure syringe, the periodontal tissue may be damaged, which prolongs postoperative pain [ 3 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study helps pediatric dentists use the ILA with CCLADS without having to consider or worry about the consequences of this technique on the dental bud of the permanent successor. Contrary to the high pressure applied by conventional ILA, slow administration of the local anesthetic solution by CCLADS is predicted to not harm the periodontal apparatus [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, studies that have used different CCLAD can be observed. Among them are The Wand® system (Milestone Scientific) (Allen et al, 2002;Muzumdar et al, 2021), the Quicksleeper™ device (Dental HiTec, Cholet, France) (Smaïl-Faugeron et al, 2019), the Sleeper One™ device (Dental Hi Research, Society and Development, v. 12, n. 7, e7212742516, 2023 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v12i7.42516 3 Tec, Cholet, France) (Elbay et al, 2016), Comfort Control Syringe™ (Dentsply International, York, PA, USA) (Deepak et al, 2017), Computer controlled Intraligamentary anesthesia (CC-ILA) (Helmy et al, 2022) and Morpheus™ (Meibach Tech) (Smolarek et al, 2020).…”
Section: Introductionmentioning
confidence: 99%